2009
DOI: 10.1089/vbz.2008.0142
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir Competence of the Redwood Chipmunk (Tamias Ochrogenys) forAnaplasma Phagocytophilum

Abstract: Granulocytic anaplasmosis (GA) is an emerging tick-transmitted disease that persists in rodent-Ixodes ricinuscomplex tick cycles across the Holarctic. Although the putative reservoir for anaplasmosis in the western United States is the dusky-footed woodrat (Neotoma fuscipes), this rodent was not shown reservoir-competent because of failure of infection from woodrats to other animals via ticks. Redwood chipmunks are common in habitats where Anaplasma phagocytophilum is common, have high PCR-and seroprevalence, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(24 citation statements)
references
References 26 publications
1
22
1
Order By: Relevance
“…phagocytophilum MRK strain, Nieto and Foley (2009) reported that squirrels belonging to the species Tamias ochrogenys could act as potential reservoirs for An. phagocytophilum.…”
Section: Introductionmentioning
confidence: 99%
“…phagocytophilum MRK strain, Nieto and Foley (2009) reported that squirrels belonging to the species Tamias ochrogenys could act as potential reservoirs for An. phagocytophilum.…”
Section: Introductionmentioning
confidence: 99%
“…Since there is no evidence of transovarial (from adult ticks to eggs) transmission, larvae do not transmit the bacterium to mammals, but infected nymphs and adult ticks do. The mammalian reservoir for A. phagocytophilum infection within the United States includes white-footed mice (Peromyscus leucopus), raccoons (Procyon lotor), gray squirrels (Sciurus carolinensis), gray foxes (Urocyon cinereoargenteus), and redwood chipmunks (69,127,165,216). A variety of other wild animals are also implicated as reservoirs (68; reviewed recently in references 208 and 218).…”
Section: Morphologymentioning
confidence: 99%
“…In the United States, certain rodent species like Tamias ochrogenys exhibit demographic characteristics, such as high population density and ability to remain infected for long periods of time, that contribute towards transmission of Anaplasma phagocytophilum, the etiological agent of human granulocytic anaplasmosis (NIETO & FOLEY, 2009). Moreover, dispersal of this rodent species may facilitate the spread of infected ticks to other vertebrate hosts (NIETO & FOLEY, 2009).…”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 99%
“…Moreover, dispersal of this rodent species may facilitate the spread of infected ticks to other vertebrate hosts (NIETO & FOLEY, 2009). The rodent species Neotoma fuscipes has been shown to be an important source of infection for the DU-1, HZ, MRK and Dog_CA strains of A. phagocytophilum.…”
Section: Molecular Detection Of Anaplasmataceae Agents Inmentioning
confidence: 99%